Trend and Variability Analysis of Sunshine Duration in Divisional Headquarters of Bangladesh (Journal of Environmental Science and Natural Resources, 2021)
In this study, Sunshine duration data of eight divisional headquarters of Bangladesh Meteorological Stations (Dhaka, Rangpur, Rajshahi, Mymensingh, Sylhet, Barishal, Khulna and Chattagram) were analyzed to evaluate the long-term changes and trends. The data used are the BMD data spanning from 1980 to 2010. The annual sunshine duration has decreased by the month of (June –September) from 1980 to 2010. Seasonal changes in sunshine duration were also analyzed where the maximum decline was found in rainy-monsoon season (June – September), the winter season (December – February), then the post-monsoon season (October – November) and the minimum in the pre-monsoon season (March – May). Analysis of observed data before and after 2000 represents the sunshine durations have decreasing trends in all divisional headquarters of Bangladesh except Chattagram station during the month of (January – December). General Circulation Model (GCM) defined that the maximum sunshine hour was decline north-east and south-west in all divisional headquarters of Bangladesh during the month of (June – September) and the minimum sunshine hour was decline in eastern part of the country during the month of (March – May).Environ. Sci. & Natural Resources, 12(1&2): 127-133, 2019